Instruments to Measure Nurses’ Knowledge And Skills in Implementing Evidence-Based Practice: A Literature Review - Wahyu Hidayat; Syahrul Syahrul (Indonesian Contemporary Nursing Journal, 2019)
Introduction: There are available instruments to measure nurses' knowledge and skills related to Evidence-Based Practice (EBP) implementation. The purpose of this study is to investigate the instrumentsto evaluate knowledge and skills of nurses in the application of evidence-based practice. Methode: Searching for resources using keywords to find instruments to measure nurses' knowledge and skills in implementing EBP in Pubmed and Willey databases, and then using Critical Assessment Capability Program (CASP) for cross sectional study as a tool to extract the publications obtained. Result: Eleven publications were analyzed descriptively, only two publications used the same instrument. But does not mean that the instruments used by other researchers are invalid. Conclusions: This literature review have not been able to explain which instrument is better to use in measuring EBP nurses' knowledge and skills. The instrument to be used needs to pay attention to the appropriateness of the contents of the instrument to the organization's organizational culture so that the results of the measurements taken can provide valid data.